Implementation of international experience of legal regulation and state management of ensuring the economic security of the state in Ukraine - Mihus, Iryna; Greben, Svitlana; Мігус, Ірина Петрівна (Scientific Center of Innovative Researches OÜ, 2023)
In modern conditions, the problem of implementing the international experience of public administration and legal regulation to ensure the economic security of the state is extremely acute, since in many spheres of social life we use the experience of the countries of the world without taking into account the peculiarities of the implementing country. The purpose of the article is to provide recommendations for Implementation of international experience of legal regulation and state management of ensuring the economic security of the state in Ukraine. The basis of the research methodology is the study of legal acts of the countries of the European Union, the United States of America, Japan, China and others in the context of ensuring economic security. The main methods that were used are the method of analysis and synthesis, comparative analysis, generalization and visualization. The main systems and models of national security of the countries of the world were systematized. Studying the international experience of public administration in ensuring the economic security of the state made it possible to single out their common (all the studied countries take care to minimize risks in important areas of public life) and distinctive (not all states have separate legal acts regulating the process of public administration in the sphere economic security) features, to analyze the peculiarities of the state management mechanism for ensuring the economic security of America, Europe and Asia. The main threats that negatively affect the economic security of Ukraine were systematized. The main areas of ensuring economic security have been systematized in accordance with the adopted "National Security Strategy of Ukraine" and the results of the analysis of the legislation of the leading countries of the world. The obtained research results should be used to improve the state management mechanism for ensuring economic security in Ukraine.
Keywords: economic security; economic security of the state; implementation; models of national security; threats